Vitamin K-dependent carboxylation regulates Ca2+ flux and adaptation to metabolic stress in β cells - Lacombe, Julie; Guo, Kevin; Bonneau, Jessica; Faubert, Denis; Gioanni, Florian; Vivoli, Alexis; Muir, Sarah M.; Hezzaz, Soraya; Poitout, Vincent; Ferron, Mathieu (Cell reports (Cambridge), 2023)
Vitamin K is a micronutrient necessary for γ-carboxylation of glutamic acids. This post-translational modification occurs in the endoplasmic reticulum (ER) and affects secreted proteins. Recent clinical studies implicate vitamin K in the pathophysiology of diabetes, but the underlying molecular mechanism remains unknown. Here, we show that mouse β cells lacking γ-carboxylation fail to adapt their insulin secretion in the context of age-related insulin resistance or diet-induced β cell stress. In human islets, γ-carboxylase expression positively correlates with improved insulin secretion in response to glucose. We identify endoplasmic reticulum Gla protein (ERGP) as a γ-carboxylated ER-resident Ca2+-binding protein expressed in β cells. Mechanistically, γ-carboxylation of ERGP protects cells against Ca2+ overfilling by diminishing STIM1 and Orai1 interaction and restraining store-operated Ca2+ entry. These results reveal a critical role of vitamin K-dependent carboxylation in regulation of Ca2+ flux in β cells and in their capacity to adapt to metabolic stress. [Display omitted] •Vitamin K-dependent carboxylation regulates glucose-stimulated insulin secretion•ERGP is a γ-carboxylated protein controlling store-operated calcium entry•ERGP γ-carboxylation reduces STIM1 and Orai1 puncta formation•Decarboxylated ERGP causes calcium overfilling in β cells and hyperinsulinemia Reduced vitamin K (VK) intake is associated with an increased risk of developing type 2 diabetes. Lacombe et al. demonstrate that VK-dependent carboxylation is necessary for β cell adaptation in mice fed a high-fat diet. The underlying mechanism involves ERGP, a carboxylated protein that regulates store-operated calcium entry in β cells.